Presentation of a new index for estimation of aromaticity in halo‐ and cyanobenzenes: The role of potential energy in aromaticity. Issue 2 (26th August 2013) - Ebrahimi, Ali; Mostafavi, Najmeh; Karimi, Pouya
<x xml:space="preserve">Abstract</x> A linear correlation has been obtained between average values of Hamiltonian kinetic energy ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zftkv67" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />K(r)</alternatives>) and potential energy ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zftkv9w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V(r)</alternatives>) calculated at the bond critical points using atoms in molecules method. This relation was used to introduce a new index ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zftkv7s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M(r)</alternatives>) for estimation of aromaticity in halo‐ and cyanobenzenes. Potential energy has different terms such as attraction between nuclei and electrons, also repulsion of electrons which affect the inertia and mobility of electrons, respectively. Therefore, contribution of potential energy in this relation must be controlled. Contribution of potential energy in aromaticity has been managed using a fitting parameter. This parameter was obtained by fitting the aromaticity stabilization energy data with values of aromaticity calculated by <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zftkvdj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M(r)</alternatives> index for halo‐ and cyanobenzenes. The contribution of potential energy in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zftkvf3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M(r)</alternatives> index is complete when molecule is nonaromatic and is negligible when molecule is antiaromatic. Indeed, molecule is aromatic when contribution of potential energy in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zftkvgn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M(r)</alternatives> index lies between above limits. © 2013 Wiley Periodicals, Inc.